2020
DOI: 10.3390/ijerph17020673
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Factors in the Working Environment, Lack of Adequate Sleep, and Musculoskeletal Pain among Nursing Unit Managers

Abstract: Background: Middle managers have not received enough attention within the healthcare field, and little is known how stressful factors in their work environment coupled with a lack of adequate sleep are related to musculoskeletal pain. The aim of this study was to examine the correlation between stressful factors in the work environment, lack of adequate sleep, and pain/discomfort in three body areas. Methods: Questionnaire was sent electronically to all female nursing unit managers (NUM) in Iceland through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(76 reference statements)
1
3
0
3
Order By: Relevance
“…In the present review, there was some evidence to suggest that greater work experience or seniority was associated with poorer sleep among HCWs, although some studies also found inverse associations. Results of previous studies provide some support for an association between greater work experience and less stress (Lam et al, 1999;Casu and Giaquinto, 2018); however overall, this finding is largely consistent with the findings of more recent research, where similarly heterogeneous associations between seniority and sleep (Sigursteinsdóttir et al, 2020) and seniority and stress-related outcomes (e.g., psychological distress and burnout) (Vargas et al, 2014;Gómez-Urquiza et al, 2017) were observed in HCWs.…”
Section: Emergent Risk Factorssupporting
confidence: 87%
“…In the present review, there was some evidence to suggest that greater work experience or seniority was associated with poorer sleep among HCWs, although some studies also found inverse associations. Results of previous studies provide some support for an association between greater work experience and less stress (Lam et al, 1999;Casu and Giaquinto, 2018); however overall, this finding is largely consistent with the findings of more recent research, where similarly heterogeneous associations between seniority and sleep (Sigursteinsdóttir et al, 2020) and seniority and stress-related outcomes (e.g., psychological distress and burnout) (Vargas et al, 2014;Gómez-Urquiza et al, 2017) were observed in HCWs.…”
Section: Emergent Risk Factorssupporting
confidence: 87%
“…Before the COVID-19 outbreak, several studies explored nurse managers' sleep problems. For example, Sigursteinsdóttir et al (2020) conducted an online survey in Iceland and found that 44% of 110 nurse managers experienced short sleep duration and 12% of them rarely had adequate sleep [10]. A study with 126 Chinese nurse managers found that the prevalence of poor sleep quality was 42.9% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Stressful situations experienced at work are related to musculoskeletal pain. A study conducted with Icelandic unit nurses concluded that daily work stress had any strong correlation with musculoskeletal pain and the places where these professionals most reported pain were in the neck and shoulder areas ( 33 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with nurses from the United Arab Emirates also verified physiological stress, by salivary cortisol levels and correlated it with the stress perceived in the work routine and, likewise, no significant association was found between the variables, although the authors concluded that lower salivary cortisol levels were related to better coping mechanisms and also emphasized that individual coping strategies were important for the health of nurses ( 34 ) . There is also a greater number of studies that evaluate stress with the use of validated instruments ( 15 , 19 - 20 , 25 , 28 , 33 ) and there are few studies of stress evaluation through cortisol with nursing professionals during the Accreditation process.…”
Section: Discussionmentioning
confidence: 99%